2007
DOI: 10.1158/1535-7163.mct-06-0705
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of nuclear receptor corepressor misfolding in acute promyelocytic leukemia cells with genistein

Abstract: We have recently reported that PML-RAR -induced mis-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…3B). Apparently, the stabilization of N-CoR protein by curcumin was mediated by an inhibition of N-CoR degradation rather than an inhibition of N-CoR misfolding as observed previously with genistein (16). Consistent with this idea, relative level of detergent-insoluble N-CoR protein in NB4 cells or 293T cells overexpressing N-CoR was increased after curcumin treatment while there was hardly any change in the level of detergent-soluble N-CoR protein ( Fig.…”
Section: Selective Inhibition Of Growth Of Apl Cells By Curcuminsupporting
confidence: 84%
See 1 more Smart Citation
“…3B). Apparently, the stabilization of N-CoR protein by curcumin was mediated by an inhibition of N-CoR degradation rather than an inhibition of N-CoR misfolding as observed previously with genistein (16). Consistent with this idea, relative level of detergent-insoluble N-CoR protein in NB4 cells or 293T cells overexpressing N-CoR was increased after curcumin treatment while there was hardly any change in the level of detergent-soluble N-CoR protein ( Fig.…”
Section: Selective Inhibition Of Growth Of Apl Cells By Curcuminsupporting
confidence: 84%
“…In our initial screening of selected compounds on APL-derived cells, we identified genistein and curcumin as potent inhibitors of growth of multiple APL-derived cells. The therapeutic effect of genistein and its underlying molecular mechanism of action have been documented previously (16). Here, we report that curcumin, a natural component of turmeric that has previously been shown to rescue the native conformation of several misfolded proteins such as the amyloid b (Ab), mutated cystic fibrosis transmembrane conductance regulator (CFTR), and truncated myelin protein zero (MPZ; refs.…”
Section: Introductionmentioning
confidence: 96%
“…It was later identified as a Ski interacting protein in yeast two-hybrid assay [10] and was also demonstrated to have an essential role in the transcriptional repression of the tumor suppressors Mad and Rb [11], [12]. Our laboratory later reported that abrogation of N-CoR-mediated transcriptional repression due to a misfolded conformation dependent loss (MCDL) of N-CoR protein was associated with the differentiation arrest of leukemic cells in Acute Promyelocytic Leukemia (APL) [13], [14], [15]. Recently, N-CoR was also reported to be essential for the differentiation of erythroid cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…Genistein (4 0 ,5,7-trihydroxy isoflavone), a natural isoflavone compound found in soy products, inhibits activation of protein tyrosine kinases and exhibits numerous effects on cell functions. For example, this compound inhibited tumor cell proliferation and metastasis, induced tumor cell differentiation, triggered cell cycle arrest at G 2 /M phase and apoptosis in some cell types, and blocked apoptosis under other circumstances [18][19][20][21][22][23][24][25][26]. Other evidence indicated that isoflavone consumption might be associated with an increased risk of HCC in women.…”
Section: Introductionmentioning
confidence: 99%